Sosialisasi dan Edukasi Anti Perundungan di Lingkungan SMP Negeri 19 Palu - Intan, Nur; Afni, Nur; Wahyunita, Wahyunita; Jamaluddin, Jamaluddin; Isnaini, Siti Haskia; Nurhasanah, Nurhasanah; Kadoy, Sofia Trivena; Lovita, Sherly; Angreni, Ayu Diah; Safitri, Suci; Saskya, Saskya; Alapi, Rahmat; Rapsanjani, Hilal; Ansari, Rezki (LPPM Universitas PGRI Argopuro Jember, 2026)
Bullying remains prevalent in schools and negatively affects students’ emotional, social, and academic development. Limited understanding of its forms, causes, impacts, and prevention strategies makes students vulnerable as both perpetrators and victims. This study aims to assess the effectiveness of anti-bullying socialization and education in improving knowledge and awareness among seventh-grade students at SMP Negeri 19 Palu. The method employed a one-group pre-test–post-test design with a health education approach, involving 107 students selected through total sampling. Instruments included questionnaires, observation sheets, and documentation. Activities were conducted in three stages: observation, implementation (presentations, educational videos, discussions, simulations, interactive games, post-test), and evaluation. Results demonstrated a significant increase in students’ understanding of bullying definitions, physical, verbal, social, and cyber forms, and preventive measures. Observations also indicated enhanced student confidence in discussing and rejecting bullying behaviors. In conclusion, the program proved effective and is recommended to be implemented regularly to foster a safe and bullying-free school environment